Reform of the Rules for the Rising Seas - Iorns, Catherine (Victoria University of Wellington Law Review, 2022)
New Zealand's existing law and policy is not adequate to provide for appropriate adaptation to the effects of climate change. There have been widespread calls for law reform, particularly to the laws affecting local government decision-making on the adoption of climate adaptation mechanisms, such as the Resource Management Act 1991 (RMA). The author is one researcher who has identified the need for law reform in this area, focusing on the (in)ability of the RMA to deal with the adaptation necessary to handle the expected effects of sea-level rise. In July 2020 an independent Resource Management Review Panel (the Randerson panel) recommended replacing the current Resource Management Act with a completely new resource management system and suite of laws. One of the topics addressed in the Panel's 531-page report is law reform for climate adaptation. The Panel recommended the adoption of a separate Climate Adaptation and Managed Retreat Act to enable better decision-making processes and results. The government has adopted the Panel's recommendations and is in the process of drafting legislation to implement them. This article addresses how well the proposed reforms address the specific needs for reform identified in the author's prior work on this topic.